Medical education, cost and policy: what are the drivers for change? - Kieran Walsh (Istituto Superiore di Sanità, 2014)
Medical education is expensive. Its expense has led many stakeholders to speculate on how costs could be reduced. In an ideal world such decisions would be made on sound evidence; however this is impossible in the absence of evidence. Sometimes practice will be informed by policy, but policy will not always be evidence based. So how is policy in the field of cost and value in medical education actually developed? The foremost influence on policy in cost and value should be evidence-based knowledge. Unfortunately policy is sometimes influenced by what might at best be termed tradition and at worst inertia. Another influence on policy will be people - but some individuals may have more influence than others. A further influence on policy in this field is events, and mainly events that have gone wrong. One final influence on emerging policy in medical education cost analysis is that of the media.